Ready or Not? Early Childhood Teachers' Challenges Facing Deep Learning in the 2025 National Curriculum - Meilia Mey mey; Edi Waluyo; Ali Formen (Universitas Pendidikan Ganesha, 2026)
The implementation of the 2025 Curriculum brings significant changes to early childhood education through a deep learning approach that emphasizes critical, creative, reflective, and adaptive thinking. However, its implementation still faces challenges, particularly in teachers’ readiness to understand and apply deep learning principles. This study aims to analyze the level of ECE teachers’ readiness in implementing deep learning, identify the major challenges encountered, and examine the relationship between teacher readiness and curriculum implementation challenges. The study employed a quantitative approach using a descriptive-correlational design. The participants consisted of 100 ECE teachers selected through purposive sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed through descriptive statistics, Pearson Product-Moment correlation, and multiple linear regression analysis. The findings revealed that teachers’ readiness was categorized as moderately ready, with major weaknesses in digital literacy and the availability of contextual teaching materials. The main challenges identified included limited curriculum training, heavy administrative workloads, and low parental involvement. The analysis demonstrated a significant negative relationship between teacher readiness and curriculum implementation challenges. These findings highlight that strengthening teacher competence through continuous professional training, mentoring, and institutional support is essential for supporting the successful implementation of Curriculum 2025 and improving the quality of ECE learning in accordance with 21st-century demands. This study highlights the need for continuous teacher professional development, particularly in digital literacy, deep learning-based instruction, and adaptive institutional support.